Effects of sex, toilet training, stress, and caffeine on nocturnal enuresis among school children in Gondar Town, the metropolitan city of Ethiopia: a community-based study in 2023 - Assimamaw, Nega Tezera; Kebede, Atnasiya Kibkab; Bazezew Genetu, Kalkidan (Frontiers in Pediatrics, 2024)
Background: Nocturnal enuresis is associated with severe social and psychological problems that affect one's self-esteem, later in life, harmed adolescent and adult life, emotional stress on the family, and poor school performance. Moreover, enuresis children may cause panic attacks, mood disorders, and depression. This study aims to assess the prevalence and associated factors of nocturnal enuresis among children aged 5-14 years in Gondar city, Northwest Ethiopia, 2023.: A community-based, cross-sectional study was conducted from April 1, 2023, to May 30, 2023. A stratified multistage sampling technique was used to select study subject from kebeles in Gondar city. The data were collected by using a structured, interviewer-administer Questionnaire. The data were entered using EPI DATA version 4.6.02 software, and processed ,and analyzed using the statistical package for the social sciences (SPSS) version 25. All variables with P ≤ 0.25 in the bivariate analysis were included in the final model of multivariate analysis. The multivariate binary logistic regression was used to assess the association between the independent and outcome variable. The direction and strength of statistical association were measured with an adjusted odds ratio along with 95% CI and a P-value < 0.05 was considered statistically significant. Result: The overall prevalence of nocturnal enuresis among children aged 5-14 years was 162(22.2%). The findings showed that being boys [AOR = 0.54; 95% CI (0.31, 0.93)], child and no toilet training practices [AOR = 2.50; 95% CI (1.02, 6.15)],Having no caffeine [AOR = 0.16; 95% CI (0.09, 0.29)], and exposure to stressful events [AOR = 20; 95% CI (11.12, 33.34)] had a significant association with nocturnal enuresis, p-value <0.05.In this study, the prevalence of nocturnal enuresis children age 5-14 years was higher than that in previous studies. Sex of child, toilet training practices, caffeine c before bed, and presences of stressful event were a significant predictor of nocturnal enuresis.